Upaya Meningkatkan Hasil Belajar IPA Materi Perubahan Sifat Benda Menggunakan Pendekatan Kontekstual Tipe Inkuiri Pada Siswa Kelas V SDN 13/I Muara Bulian - Halimah Halimah (Peneliti.net, 2022)
The research used was Classroom Action Research (CAR) which was carried out in two cycles, where each cycle consisted of two meetings. The research setting is the fifth grade students of SD Negeri 13/I Muara Bulian for the 2016/2017 academic year, with a total of 26 students. The research instrument used was an observation sheet on teacher and student activities in learning, and student evaluation tests to determine student learning outcomes at the end of each meeting. Data analysis techniques used, distribution, frequency, percentage, and interpretation. The results of the study prove that the inquiry-type contextual approach can improve student learning outcomes on the material of changing the nature of objects in class V SD Negeri 13/I Muara. Teacher activity increased, namely the average of the first cycle was 72.75% increased to 87.72% in the second cycle. The average student activity in the first cycle was 85% increased to 97.50% in the second cycle. Student learning outcomes increased, namely in the first cycle evaluation 77.11 increased to 96.92 in the second cycle evaluation. Classical completeness in the first cycle reached 61.54% increased to 100% in the second cycle. Based on the results of this study, it was concluded that the learning outcomes of science learning material on Changes in the Nature of Objects using the Inquiry Type Contextual Approach in fifth grade students of SD Negeri 13/I Muara increased and the hypothesis was accepted